2011
DOI: 10.1007/s11661-011-0829-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alloying Elements on High-Temperature Oxidation and Sticking Occurring During Hot Rolling of Modified Ferritic STS430J1L Stainless Steels

Abstract: In the present study, mechanisms of sticking that occurs during hot rolling of modified STS430J1L ferritic stainless steels were investigated by using a pilot-plant-scale rolling machine, and the effects of alloying elements on sticking were analyzed by the high-temperature oxidation behavior. The hot-rolling test results indicated that the Cr oxide layer formed in a heating furnace was broken off and infiltrated the steel, thereby forming Cr oxides on the rolled steel surface. Because the surface region witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…[ 5 ] In addition, the nucleation and growth of Cr oxides are promoted by Si element in the steel. [ 6 ] Therefore, the microstructure of oxide scale is affected by the alloying elements, resulting in the sticking is also affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] In addition, the nucleation and growth of Cr oxides are promoted by Si element in the steel. [ 6 ] Therefore, the microstructure of oxide scale is affected by the alloying elements, resulting in the sticking is also affected.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition, the nucleation and growth of Cr oxides are promoted by Si element in the steel. [6] Therefore, the microstructure of oxide scale is affected by the alloying elements, resulting in the sticking is also affected.In hot rolling at high temperatures (500-1200 °C), [7] water is used as a coolant in several stages of hot rolling such as finishing rolling and laminar flow cooling, leaving the ferritic stainless steel in a high-temperature water vapor atmosphere. The effect of water vapor on high-temperature oxidation of ferritic stainless steel has been studied by some scholars.…”
mentioning
confidence: 99%
“…7 However, during the hot rolling of ferritic STSs with a high Cr content, oxide flakes form and stick to the rollers, 4 deteriorating the surface of the STSs. 8,9 Because the surface quality is critical, STSs with indented surfaces have significantly diminished value. 10,11 Therefore, many engineers have tried to explain the fundamental mechanisms 12,13 and address the sticking failure problem with empirical control of alloying elements, 9 structural analysis, 11 processing parameter controls, 10 and replication of hot-rolling processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the hot rolling of ferritic STSs with a high Cr content, oxide flakes form and stick to the rollers, deteriorating the surface of the STSs. , Because the surface quality is critical, STSs with indented surfaces have significantly diminished value. , Therefore, many engineers have tried to explain the fundamental mechanisms , and address the sticking failure problem with empirical control of alloying elements, structural analysis, processing parameter controls, and replication of hot-rolling processes . Kim et al suggested failure mechanisms with different types of commercial STSs on the basis of an ex situ elemental image analysis of the microstructure of the scale and the exposed fractured surface.…”
Section: Introductionmentioning
confidence: 99%